Molecular Regulation of the Melatonin Biosynthesis Pathway in Unipolar and Bipolar Depression - Dmitrzak-Weglarz, Monika; Banach, Ewa; Bilska, Karolina; Narozna, Beata; Szczepankiewicz, Aleksandra; Reszka, Edyta; Jablonska, Ewa; Kapelski, Paweł; Skibinska, Maria; Pawlak, Joanna (Frontiers in Pharmacology, 2021)
Melatonin is a neurohormone that maintains the circadian rhythms of the body. By regulating the secretion of other hormones and neurotransmitters, it acts as a pleiotropic modulator, e.g., reproductive, immune, cardiovascular, sleep and wake systems and mood. Thus synthetic melatonin has become an essential component in the treatment of depressive disorders. Although we know the pathway of melatonin action in the brain, we lack comprehensive cross-sectional studies on the periphery of depressed patients. This study aims to analyze comprehensively the differences between healthy control (n=84) and unipolar and bipolar depression patients (n=94), including an analysis of the melatonin pathway at the level of the genes and serum biomarkers. An innovative approach is a pilot study based on gene expression profiling carried out on clinical and cell culture models using agomelatine and melatonin. We confirm the melatonin biosynthesis pathway's molecular regulation dysfunctions, with a specific pattern for unipolar and bipolar depression, at the AANAT gene, its polymorphisms (rs8150 & rs3760138) and examined the serum biomarkers (serotonin, AANAT, ASMT, melatonin). The biological pathways analysis uncovered pathways and genes uniquely altered after agomelatine treatment in a clinical model and melatonin treatment in a cell culture model. In both models we confirmed the immunomodulatory effect of melatonin agents in depression.